Succinic acid as a coordination modulator for DMSO-free low-dimensional red-emitting tin perovskites - Akhil Sreevalsan; Woo Hyeon Jeong; Yifan Yu; Cheong Beom Lee; Gunhee Kim; Jongbeom Kim; Hochan Song; Hong In Jeong; Gyeong Eun Seok; Dong-Won Kang; Myoung Hoon Song; Kyeounghak Kim; et al. (Chemical Engineering Journal, 2026)

Machine learning-based spatiotemporal modeling and health risk assessment of PAHs and metals in an industrial city - Jeong-Tae Ju; Sang-Jin Lee; In-Gyu Cho; Ji Yoon Choi; Taekyu Kim; Sung-Deuk Choi (Atmospheric Environment, 2026)

Quadruple co-infection with Mycobacterium tuberculosis complex and M. kansasii in a chronically immunosuppressed cat - Sungyoung Choi; Soo-Nyun Choi; Tak Gyeom Lee; Sungweon Ryoo; Ji-Hoon Kwak; Kun-Woo Kim; Tae In Park; Woo-Jin Song; Eun-Joo Lee; Kyu-Shik Jeong (Veterinary Research Communications, 2026)

Part-load operation of the Supercritical CO2 power cycle for Hybrid Micro Modular reactor with control strategy optimization using GAMMA+ - Sungwook Choi; In Woo Son; Jeong Ik Lee (Annals of Nuclear Energy, 2026)

Allergenicity of edible insect proteins: Cross-reactivity, processing effects, and food safety considerations - Jae Hoon Lee; Ji Yoon Cha; Seonmin Lee; Yea-Ji Kim; Jeong-Heon Kim; Dong Hyun Keum; Hae In Yong; Min Hyeock Lee; Yun-Sang Choi (Food Chemistry, 2026)

Hydramethylnon induces synergistic toxicity of pyrethroid mixtures in human lung epithelial cells - Hye-Jin Jeong; Hye-In Park; Tae-Rim Im; Ju-Hui Im; Seung Min Choi; Chang-Ik Choi; Myungwon Seo; Yong Joo Park (Toxicological Research, 2026)

Application of Fibronectin-Coated Microparticles for Isolation of Human iPSC-Derived MSCs - Jae Hyeok Jang; In Sun Hwang; Ji Seob Kim; Sunjun Lee; Min Hee Moon; Bowon Kim; Seo Jeong Kim; Jongho Choi; Young Her; Soo-Hong Lee; Byung-Hyun Cha (Tissue Engineering and Regenerative Medicine, 2026)
BACKGROUND : Bone marrow–derived MSCs (BMMSCs) are limited by availability, donor variability, and age-related decline, highlighting the need for alternative MSC sources. Induced pluripotent stem cells (iPSCs) offer a scalable solution. This study introduces a novel three-dimensional culture platform based on fibronectin (FN)-coated microparticles to efficiently derive and expand human iPSC-derived MSCs (iMSCs). METHODS : The system utilizes FN-coated non-porous (CytoDex) and porous (CytoPore) microparticles. FN coating efficacy on microparticle was confirmed using Rhodamine-labeled FN and confocal microscope. Base on various molecular cell biological experiment, the utilization of FN-coated CytoDex and CytoPore leverages an expanded surface area to improve iMSCs isolation. The characteristics and cell behaviors of iMSCs generated from FN-coated CytoDex and CytoPore was evaluated by immunophenotype analysis, cell proliferation, and senescence related assays. In vivo tissue regeneration was evaluated by microcomputed tomography and histopathological analyses. RESULTS : The porous microparticle CytoPore significantly enhanced FN coating efficiency, cell attachment, and proliferation compared to CytoDex. FN-coated CytoPore enabled the selective isolation of a high-purity MSC population from spontaneously differentiated iPSCs (SD-iPSCs) by day 7, confirmed by distinct morphology and mesodermal marker expression. The resulting iMSCs exhibited immunophenotypic characteristics comparable to adult MSCs, along with superior proliferative capacity, extended telomere length, and minimal senescence over 10 passages, in contrast to BMMSCs. Furthermore, iMSCs demonstrated effective in vivo tissue regeneration in an osteochondral defect model. CONCLUSION : This novel FN-coated microparticle-based 3D culture platform enables efficient, large-scale production of high-quality iMSCs and holds strong potential for clinical applications in stem cell therapeutics and regenerative medicine.

Effects of Clinostat rotation on stem morphology of Pisum Sativum - Sang-Min Kim; Jung-Hoo Kook; Jeong-In Choi; Oluwasegun Moses Ogundele; Won-Cheol Lee; Hyeon-Tae Kim (Life Sciences in Space Research, 2026)

Structural degradation of kraft lignin under long-term UV irradiation: Molecular, spectroscopic, and surface-level insights - Chaeeun Kim; Chaewoo Jeong; Jungkyu Kim; In-Gyu Choi; Hyo Won Kwak (Biomass and Bioenergy, 2026)

Probiotic-Derived Strain-Specific Metabolites Ameliorate Metabolic Dysfunction–Associated Steatotic Liver Disease through Modulation of the Gut-Liver Axis - Sang Jun Yoon; Jieun Choi; Sung-Min Won; Jeong Seok Yu; Hee Young Kim; Hyun Chae Joung; In Gyu Park; Jung A Eom; Sang Hak Han; Do Yup Lee; Ki Tae Suk (Probiotics and Antimicrobial Proteins, 2026)

Facile eco-friendly sol-gel synthesis of highly monodispersed Zn@silica nanospheres with dual antibacterial mechanism against multidrug-resistant bacteria - Yesul Jeong; Hyeran Kim; Soon Chang Lee; Ha-Rim An; Jong-Seong Bae; Yunju Choi; Byoungchul Son; Ji-In Park; Da-Hye Kim; Jiwon Seo; Eui-Jeong Han; Ji-Hyun Lee; et al. (Chemical Engineering Journal, 2026)

RNAseq-based molecular insights into three insecticide resistances in Laodelphax striatellus: Structural perspective on CYP6ER2 in detoxification - Minyoung Choi; Murtaza Khan; In-hong Jeong; Juil Kim (Pesticide Biochemistry and Physiology, 2026)

Nuclear receptor ERR contributes to imidacloprid resistance by upregulating cytochrome P450 in Nilaparvata lugens - Woo-Ram Park; Byungyoon Choi; Nanthini Sadasivam; Hui-Jin Bae; Sunmin Kim; Eunae Kim; Hueng-Sik Choi; In-Hong Jeong; Don-Kyu Kim (Insect Biochemistry and Molecular Biology, 2026)

Standardized olive pomace juice ameliorates scopolamine-induced cognitive decline in C57BL/6 mice via AMPKα-SIRT1-PGC1α and CREB-BDNF-TrkB signaling pathways - Ye-Lim You; Ha-Jun Byun; Namgil Kang; Min Soo Lee; Jeong-In Lee; Ilbum Park; Hyeon-Son Choi (Food Bioscience, 2026)

A single urine test-based SERS–AI–BAM for on-site multiple cancer diagnosis and metabolite profiling - Hyo Jeong Seo; Jun Young Kim; Vo Thi Nhat Linh; Boyou Heo; Jun-Young Yang; Rowoon Park; In Woong Han; Sung-Gyu Park; Min-Young Lee; Samjin Choi; Ho Sang Jung (Chemical Engineering Journal, 2026)

Molecular biomarkers associated with environmental naphthalene exposure in the respiratory system - Hye-Jeong Han; Amartuvshin Baasankhuu; Bogun Kim; Angela Astrid Sekar Prameswari; Karina Kalani; Paolo Panza; Sangwoo Lee; Woo-Keun Kim; In-Geol Choi; Cheol-Hee Kim; Hyun-Taek Kim (Science of The Total Environment, 2026)

Ferroptotic stress-guided glutathione dynamics profiling identifies melatonin priming as a potential mesenchymal stem cell strategy for asthma therapy - Hyun Jun Im; Seok Woo Ha; Keunhong Jeong; Jinwon Lee; Chae-Min Ryu; Hyungu Kwon; Jihye Kim; Yi-Xi Gong; HongDuck Yun; YongHwan Kim; Ji-Woong Shin; Hye-Mi Kim; et al. (Chemical Engineering Journal, 2026)

Seasonal and spatial distributions of polycyclic aromatic hydrocarbons in surface water of the Taehwa River in the largest industrial city in South Korea - In-Gyu Cho; Hye-Ok Kwon; Sung-Hee Seo; Joo-Yeon Oh; Eun-Jeong Park; Sung-Deuk Choi (Environmental Monitoring and Assessment, 2025)

Hybrid W-MgF2/graphene photothermal membrane for efficient solar-driven desalination - Ga Eun Lee; Jinsoo Cho; In-Young Jung; Da Seul Kim; Seok Joon Kwon; Won Jun Choi; Kyung Guen Song; Hak Ki Yu; Jeong Min Baik (Desalination, 2025)

Development of a feedback-regulated temperature control system to enable supercooling reversion in beef preservation - Seokhyeon Yun; Taeho Kim; In-U Jeong; Song-Yi Choi; Soyeon Kim; Jin Hong Mok; Taiyoung Kang (Innovative Food Science & Emerging Technologies, 2025)

Spatiotemporally adjustable hybrid hydrogels interconnected by 2D MXene for combinatorial therapy of infected diabetic wounds - Mrinmoy Karmakar; Sungyun Kim; Han-Jun Kim; Ji Won Huh; Da In Jeong; Eunseo Park; Seongeun Kim; Eun-Hye Hong; Jin Hyeong; Dae-Joon Kim; Hye Kyu Choi; Junmin Lee; et al. (Chemical Engineering Journal, 2025)

Cation adsorption strategy to increase the impregnation limit of thermally conductive alumina filler in adhesives: mass-producible and eco-friendly scheme for direct industrial application - Yechan Chang; Ahyeon Choi; Dong-In Shin; Hye Sun Park; Jisung Lee; Sooyeol Jeong; Ji-In Park; Ji Yong Bae; I Jong Kim; Sung Woo Lee; Jongchan Lee; Sangyul Baik; et al. (Chemical Engineering Journal, 2025)

Baricitinib-loaded separable microneedle array patch (S-MAP) based on hyaluronic acid for alopecia areata therapy - Da In Jeong; Song Yi Lee; Sungyun Kim; Su-Min Jo; HeeSeon Yang; Jieun You; ChaeRim Hwang; Ji Won Huh; Yeoung Eun Choi; Wonjun Jo; In-Jeong Choi; Hae-Jin Hu; et al. (Carbohydrate Polymers, 2025)

Improved thermal stability of NbCoSn half-Heusler compounds via Sb doping-induced complementary point defect evolution - Kyuseon Jang; Poulumi Dey; Biswanath Dutta; Hail Park; Ji-Hee Son; Jeong-In Jang; Mohammed Kamran Bhat; Hanhwi Jang; Hyungsub Kim; Jungwoo Choi; Siyuan Zhang; Ruben Bueno Villoro; et al. (Chemical Engineering Journal, 2025)

Long-acting injectable delivery system comprising ordered mixed drug aggregates with deaggregating and uniformly embeddable viscoelastic -polysaccharide solutions - Jun Soo Park; Dong Gun Lee; Jin Hyuk Myung; Min Young Jeong; In Gyu Yang; Gi Yeong Lee; Ji Won Yeo; Chae Won Park; Jin Hwan Kim; Ye Bin Shin; Myoung Jin Ho; Sung Giu Jin; et al. (Carbohydrate Polymers, 2025)

Seasonal dynamics of picocyanobacteria and bloom-forming cyanobacteria in Daechung Reservoir, Korea - Hye Jeong Choi; In-Chan Choi; So Hyun Cho; Eun-mi Hong; Jay Jung Lee (Paddy and Water Environment, 2025)

Spatial variations in organic matter sources and biogeochemical processes in the East Sea - Jiyoung Choi; Bo-Yeon Yi; Yuri Kim; Eun-Je Jeong; In-Kwon Um (Frontiers in Marine Science, 2025)
In this study, the spatial variations in total organic carbon (TOC), stable carbon isotopes (δ¹³Corg), C/N ratios, and nitrogen isotopes (δ¹⁵Norg) in East Sea sediments are examined to elucidate the sources, preservation, and diagenetic processes of organic matter. To this end, surface sediment samples were collected from the coastal regions of the East Sea using a box corer and analyzed for TOC, TON, stable isotopes (δ¹³C, δ¹⁵N), and grain size. The study region is categorized into three zones based on sediment characteristics: Zone A (straits), Zone B (northern coastal regions), and Zone C (central Ulleung Basin). Zone A, characterized by coarse sediments and dynamic hydrodynamic conditions, exhibits the lowest TOC (0.67%) and enriched δ¹³Corg values (-20.67‰). Zone B, influenced by coastal inputs, has moderate TOC (2.09%), slightly depleted δ¹³Corg (-21.09‰), and higher C/N ratios (6.30). Zone C, dominated by fine-grained mud sediments, features slightly lower TOC (1.96%), along with the most depleted δ¹³Corg (-21.86‰). Stable isotope analyses reveal that autochthonous particulate organic matter (POM) from marine phytoplankton is the primary source of organic matter in the East Sea. δ¹³Corg values (-23.15‰ to -20.33‰) align with phytoplankton-derived POM (-25‰ to -22‰), highlighting significant marine primary production contributions. In contrast, allochthonous inputs from atmospheric deposition, the Tsushima Warm Current, and rivers contribute approximately 82 gC/m²/year compared to 273 gC/m²/year from autochthonous sources. Seasonal δ¹³C variations are strongly correlated with peaks in primary productivity during spring and autumn. The study reveals differences between coastal (Zone B) and offshore (Zone C) regions in productivity regimes, nutrient utilization, and depositional settings. Coastal regions with high productivity show enriched δ¹³Corg, while offshore areas preserve isotopically lighter organic matter owing to stable depositional environments. Understanding the biogeochemical processes in the East Sea is essential for elucidating carbon cycling and its ecosystem implications. As a marginal sea with unique sedimentary dynamics, the East Sea serves as a natural laboratory for studying organic matter preservation. The findings provide insights into past and present carbon cycling and support predictions of future environmental changes under shifting climatic conditions.

RNA-seq-based identification of imidacloprid resistance mechanisms in Nilaparvata lugens and development of diagnostic tools for the CYP6ER1 variant - Minyoung Choi; Murtaza Khan; Changhee Han; In-hong Jeong; Nakjung Choi; Juil Kim (Pesticide Biochemistry and Physiology, 2025)

Development of advanced polyacrylonitrile fiber-based adsorbents for heavy metal ion removal through electron beam irradiation followed by amination - Minho Son; Jong-Seok Park; Sung-In Jeong; Byoung-Min Lee; Jae-Hak Choi; Joon-Pyo Jeun (Journal of Water Process Engineering, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Development of a comprehensive air risk index and its application to high spatial-temporal health risk assessment in a large industrial city - Sang-Jin Lee; In-Gyu Cho; Ho-Young Lee; Jeong-Tae Ju; Hye-Jung Shin; Sung-Deuk Choi (Environmental Pollution, 2025)

PM exposure during pregnancy affects childhood asthma via placental epigenetic changes: Neuronal differentiation and proliferation and Notch signaling pathways - Hyo-Bin Kim; Si Hyeon Lee; Dae Yeol Yang; Seung-Hwa Lee; Jeong-Hyun Kim; Hwan-Cheol Kim; Kil Yong Choi; So-Yeon Lee; Song-I Yang; Dong In Suh; Youn Ho Shin; Kyung Won Kim; et al. (Environmental Pollution, 2025)

Biogeochemical cycling of sedimentary organic carbon and benthic nutrient fluxes in the semi-enclosed Jinhae Bay, Korea: insights into benthic-pelagic coupling - Sung-Uk An; Kyung-Tae Kim; Sung-Han Kim; Ju-Wook Baek; Hyun-Jeong Jeong; Chul-In Sun; Jin Young Choi; Sokjin Hong; Dae In Lee; Jae Seong Lee (Frontiers in Marine Science, 2025)
The mineralization of organic matter at the sediment plays a crucial role in ecosystem functioning by facilitating the biogeochemical cycling of carbon and nutrients. This process not only supports nutrient availability for primary production but also regulates the long-term storage of carbon within sediments. To understand the biogeochemical processes associated with organic matter mineralization and nutrient regeneration, we estimated total and diffusive sediment oxygen uptake rates, benthic nutrient fluxes, and organic carbon (OC) budgets at four sites in the semi-enclosed Jinhae Bay (JB). The total oxygen uptake (TOU) rates ranged from 38.4 to 49.6 mmol O 2 m –2 d –1 , and diffusive oxygen uptake (DOU) rates ranged from 12.3 ± 1.8 to 15.1 ± 1.4 mmol O 2 m –2 d –1 . The average ratio of TOU : DOU ranged from 3.12 to 3.28 over JB, which suggests significant benthic faunal activities in JB sediments. The vertical flux of organic carbon ranged from 45.5 ± 7.0 to 93.0 ± 25.3 mmol C m -2 d –1 , and mainly consisted of biodeposits associated with aquaculture activities. The burial flux into the sediment ranged from 3.96 ± 1.00 to 7.17 ± 1.64 mmol C m –2 d –1 , and burial efficiencies were 4.25 to 15.8%, which indicated that deposited organic carbon was either mineralized in surface sediment before burial or laterally transferred by resuspension. The benthic nutrient fluxes at four sites ranged from 1.50 to 2.07 mmol m –2 d –1 for nitrogen, from 0.02 to 0.05 mmol m –2 d –1 for phosphate, and from 6.72 to 9.11 mmol m –2 d –1 for silicate. The benthic nitrogen and phosphate fluxes accounted for 82.1 to 149% and 23.1 to 57.6%, respectively, of the required levels for primary production in the water column. Our results suggest that OC oxidation in the JB sediment may significantly contribute to the biogeochemical OC cycles and tight benthic–pelagic coupling associated with nutrient regeneration.

Single oral toxicity assessment and phytochemical analysis of the Ficus erecta Thunb. Leaves extract - Yu Jin Kim; Mee-Young Lee; Hyun Ji Park; Eunjin Sohn; Woo-Young Jeon; Sae-Rom Yoo; In Suk Choi; Joo-Hwan Kim; Soo-Jin Jeong (Toxicon, 2025)

Dexamethasone nanocrystals-embedded hydroxypropyl methylcellulose hydrogel increases cochlear delivery and attenuates hearing loss following intratympanic injection - Min Young Jeong; Subin Kim; Hye Rim Kim; Jiae Jeon; Seong Su Won; Keum-Jin Yang; Jun Soo Park; In Gyu Yang; Dong Geon Lee; Jin Hyuk Myung; Yoon-Gyoon Kim; Sung Giu Jin; et al. (Carbohydrate Polymers, 2024)

Daily and seasonal changes of sap flow in Gamhong apple cultivar and estimate the tree-level transpiration using Penman-Monteith reference evapotranspiration - Narayan Bhusal; Louis S. Santiago; Joncheon Lee; Sanghak Jeong; In Hee Park; Byeong-Ho Choi; Hun-Joong Kweon; Su-Gon Han; Tae-Myung Yoon (South African Journal of Botany, 2024)

A new neo-lignan from culture broth of Phellinus linteus and its dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Ji-Yul Kim; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Nationwide evaluation of microplastic properties in municipal wastewater treatment plants in South Korea - Jae-Ho Lee; So-Jeong Cheon; Chang-Soo Kim; Soo-Hyun Joo; Ki-In Choi; Dong-Hwan Jeong; Soo-Hyung Lee; Jeong-Ki Yoon (Environmental Pollution, 2024)

Nationwide monitoring of legacy and emerging persistent organic pollutants and polycyclic aromatic hydrocarbons along the Korean coast - Gyojin Choo; Sol Choi; In-Seok Lee; Jeong-Eun Oh (Marine Pollution Bulletin, 2024)

Ultrathin silica-encapsulated perovskite nanocrystals for high color purity mechanoluminescence - Kyung Sik Yoo; Hong In Jeong; Sujoy Bandyopadhyay; Seo-Jin Ko; Dong-Won Kang; Jihoon Lee; Hyosung Choi (Chemical Engineering Journal, 2024)

Enhancing acetaminophen removal through persulfate activation with ZnCl2-SPI biochar: A study on reactive oxygen species contribution according to acetaminophen concentration - Heejin Yang; Gyu-Ri Choi; Yoo Jae Jeong; In Sun Cho; Seong-Jik Park; Chang-Gu Lee (Chemical Engineering Journal, 2024)

Carboxymethyl cellulose-based rotigotine nanocrystals-loaded hydrogel for increased transdermal delivery with alleviated skin irritation - Jun Soo Park; Jae Hee Seo; Min Young Jeong; In Gyu Yang; Ji Seong Kim; Jin Hwan Kim; Myoung Jin Ho; Sung Giu Jin; Min Koo Choi; Yong Seok Choi; Myung Joo Kang (Carbohydrate Polymers, 2024)

Exploring pharmacokinetics and herb-drug interactions of an herbal extract mixture derived from Poria cocos and Morus alba L. - So Yeong Yun; Jeong In Seo; Sang Zin Choi; Ja Young Ryu; Ah Yeon Park; Han Gon Choi; Hye Hyun Yoo (Journal of Pharmaceutical Investigation, 2024)

Three undescribed dimeric ferulates from the culture broth of Phellinus linteus and their dengue virus type-2 inhibition activity - Young-Hee Kim; Dae-Cheol Choi; Dae-Won Ki; Won-Gi Seo; Jae-Hyoung Song; Hyun-Jeong Ko; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2024)

Integrating chemical and biological technologies in upcycling plastic waste to medium-chain α,ω-Diacid - In-Seok Yeo; Kang-Seok Go; Woo-Young Jeon; Min-Jeong Jang; Hye-Jeong Lee; Sung-Hwa Seo; Young Su Kim; HyunA Park; Byung-wook Min; Kyungmoon Park; Yung-Hun Yang; Kwon-Young Choi; et al. (Journal of Cleaner Production, 2024)

Two-in-one strategy: Discretely functionalized electrolyte additive for stable lithium metal batteries coupled with Ni-rich cathode - Yong Min Kim; Jeong In Choi; Bo Keun Park; Ji Woo Han; Jong-Won Lee; Hyun-seung Kim; Ki Jae Kim (Chemical Engineering Journal, 2024)

A comparison of the nutritional quality of ready-to-cook meals and conventional home-cooked meals in Korea - Eunji Choi; Sung-Won Yoon; Jung-Ah Shin; In-Hwan Kim; Jeehye Sung; Jang-Hyuk Ahn; Hyun-Jeong Kim; Dong Won Seo; Sam-Pin Lee; Jo-Won Lee; Bo Kyung Moon; Sojung Kim; et al. (International Journal of Gastronomy and Food Science, 2024)

Estimation of the electrical conductivity of saturated paste from soil–water extracts of coastal saline paddy soils using random forest and multiple regression models - Hyun-Jin Park; Nuri Baek; Bo-Seong Seo; Young-Jae Jeong; Hye In Yang; Se-In Lee; Kwang-Sik Yoon; Han-Yong Kim; Woo-Jung Choi (Journal of Soils and Sediments, 2024)

Disinfection efficiency of chlorine dioxide and peracetic acid against MNV-1 and HAV in simulated soil-rich wash water - Zhaoqi Wang; Daseul Yeo; Hyojin Kwon; Yuan Zhang; Danbi Yoon; Soontag Jung; Md. Iqbal Hossain; Myeong-In Jeong; Changsun Choi (Food Research International, 2024)

Improving spray performance of vehicle disinfection systems in livestock farms using computational fluid dynamics analysis - Lak-yeong Choi; Se-yeon Lee; Jinseon Park; Se-woon Hong; Kehinde Favour Daniel; Hyo-hyeog Jeong; In-bok Lee (Computers and Electronics in Agriculture, 2023)

Dynamic response of bacterial communities to Microcystis blooms: A three-year study - Ve Van Le; Mingyeong Kang; So-Ra Ko; Seonah Jeong; Chan-Yeong Park; Jay Jung Lee; In-Chan Choi; Hee-Mock Oh; Chi-Yong Ahn (Science of The Total Environment, 2023)

Monitoring of foodborne viruses in pre- and post-washed root vegetables in the Republic of Korea - Sunho Park; Md Iqbal Hossain; Soontag Jung; Zhaoqi Wang; Daseul Yeo; Seoyoung Woo; Yeeun Seo; Myeong-In Jeong; Changsun Choi (Food Control, 2023)

Development of an In Vitro Model for Inflammation Mediated Renal Toxicity Using 3D Renal Tubules and Co-Cultured Human Immune Cells - Mi-lang Kyun; Tamina Park; Hyewon Jung; Inhye Kim; Ji-In Kwon; Seo Yule Jeong; Myeongjin Choi; Daeui Park; Yu Bin Lee; Kyoung-Sik Moon (Tissue Engineering and Regenerative Medicine, 2023)

Enhancing Viability of Human Embryonic Stem Cells during Cryopreservation via RGD-REP-Mediated Activation of FAK/AKT/FoxO3a Signaling Pathway - Jeong Hee Kim; Jeong In Choi; Young Hyun Che; Su Haeng Sung; Hojae Lee; Sun Lee; Jae-Hoon Park; Yun-Il Lee; Young-Sam Lee; Won Bae Jeon; Yong Jun Kim (Tissue Engineering and Regenerative Medicine, 2023)

Quantification and health risk assessment of ochratoxin A in dried fruit, spices, and coffee - In Min Hwang; Ji Young Jeong; Boyeon Park; Ji Yeon Choi; Naeem Khan; Nargis Jamila; Bo Ryun Yoon; Jae Sung Kim (Food Additives & Contaminants: Part A, 2023)

Detection of microplastic traces in four different types of municipal wastewater treatment plants through FT-IR and TED-GC-MS - Jae-Ho Lee; Min-Jung Kim; Chang-Soo Kim; So-Jeong Cheon; Ki-In Choi; Juyang Kim; Jaehak Jung; Jeong-Ki Yoon; Soo-Hyung Lee; Dong-Hwan Jeong (Environmental Pollution, 2023)

Optimization of an approach to detect low-concentration MNV-1 and HAV from soil-rich or non-soil post-washing water containing various PCR inhibitory substances - Zhaoqi Wang; Md Iqbal Hossain; Daseul Yeo; Seoyoung Woo; Yeeun Seo; Soontag Jung; Hyojin Kwon; Myeong-In Jeong; Changsun Choi (Food Control, 2023)

Development and application of a reverse transcription droplet digital PCR assay for detection and quantification of Plantago asiatica mosaic virus - Hyo-Jeong Lee; Sena Choi; In-Sook Cho; Ju-Yeon Yoon; Rae-Dong Jeong (Crop Protection, 2023)

Simulation of contamination and elimination of Escherichia coli, Listeria monocytogenes, and Murine norovirus 1 (MNV-1) from the washing process when handling of potatoes - Hyojin Kwon; Zhaoqi Wang; Hyelim Gu; Sumin Hwang; Youngmin Hwang; Jihoon An; Dong-Un Lee; Myeong-In Jeong; Changsun Choi (International Journal of Food Microbiology, 2023)

Coupling of δ13C and δ15N to understand soil organic matter sources and C and N cycling under different land-uses and management: a review and data analysis - Hyun-Jin Park; Nuri Baek; Sang-Sun Lim; Young-Jae Jeong; Bo-Seong Seo; Jin-Hyeob Kwak; Sang-Mo Lee; Seok-In Yun; Han-Yong Kim; Muhammad A. Arshad; Woo-Jung Choi (Biology and Fertility of Soils, 2023)

Unveiling reactive origin through the in situ 2D core–shell formation, Ni(CN)2@Ni2P, derived from Hofmann-type MOF for water oxidation - Jiwon Kim; Hyung Wook Choi; Jongseok Kim; Jung Hyeon Yoo; Dong In Jeong; Ui Young Lee; Hyuk Choi; Bong Kyun Kang; Ki-Seok An; Hyun You Kim; Dae Ho Yoon (Chemical Engineering Journal, 2023)

Correction to: Cerebral glucose metabolism differs according to future weight change - Jeong Mi Kim; Minhee Jang; Eun Heui Kim; Mijin Kim; Su Jung Choi; Keunyoung Kim; Kyoungjune Pak; Yun Kyung Jeon; Sang Soo Kim; Bo Hyun Kim; Seong-Jang Kim; In Joo Kim (Brain Imaging and Behavior, 2023)

Understanding protein digestion in infants and the elderly: Current in vitro digestion models - Seonmin Lee; Kyung Jo; Hyun Gyung Jeong; Yun-Sang Choi; Hae In Yong; Samooel Jung (Critical Reviews in Food Science and Nutrition, 2023)

Estimation of ventilation rate in a piglet house considering ventilation system characteristics - Young-bae Choi; Jun-gyu Kim; Jeong-hwa Cho; Sang-yeon Lee; Se-jun Park; Cristina Decano-Valentin; Deuk-young Jeong; In-bok Lee (Biosystems Engineering, 2023)

Characteristics of pork emulsion gel manufactured with hot-boned pork and winter mushroom powder without phosphate - Hyun Gyung Jeong; Kyung Jo; Seonmin Lee; Hae In Yong; Yun-Sang Choi; Samooel Jung (Meat Science, 2023)

High-pressure induced structural modification of porcine myofibrillar protein and its relation to rheological and emulsifying properties - Min Hyeock Lee; Hae In Yong; Yun Jeong Kim; Yun-Sang Choi (Meat Science, 2023)

Stability and inactivation of SARS-CoV-2 on food contact surfaces - Soontag Jung; Dong-Hwi Kim; Hee-Seop Ahn; Hyeon-Jeong Go; Zhaoqi Wang; Daseul Yeo; Seoyoung Woo; Yeeun Seo; Md Iqbal Hossain; In-Soo Choi; Sang-Do Ha; Changsun Choi (Food Control, 2023)

Antiviral activity of canine interferon lambda 3 expressed using a recombinant adenovirus against canine coronavirus, canine parvovirus, and canine distemper virus - Dong-Hwi Kim; Sang-Hoon Han; Hyeon-Jeong Go; Da-Yoon Kim; Jae-Hyeong Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Veterinary Research Communications, 2022)

Activation of galactose utilization by the addition of glucose for the fermentation of agar hydrolysate using Lactobacillus brevis ATCC 14869 - Godfrey Mwiti; In-Seok Yeo; Kyung-Hun Jeong; Hyung-Seok Choi; Jaehan Kim (Biotechnology Letters, 2022)

Characterization of non-solvent- and thermal-induced phase separation applied polycaprolactone/demineralized bone matrix scaffold for bone tissue engineering - Soo in Kim; Na Eun Kim; Sunjae Park; Joo Hee Choi; Younghun Lee; Gayeong Jeon; Jeong Eun Song; Gilson Khang (In vitro models, 2022)

Land use types with different fertilization management affected isotope ratios of bulk and water-extractable C and N of soils in an intensive agricultural area - Young-Jae Jeong; Hyun-Jin Park; Byeong-Jun Jeon; Bo-Seong Seo; Nuri Baek; Hye In Yang; Jin-Hyeob Kwak; Sang-Mo Lee; Woo-Jung Choi (Journal of Soils and Sediments, 2022)

Galuteolin, identified in the extract of thymus quinquecostatus flowers, is involved in inhibiting melanin biosynthesis in B16/F10 melanoma cells - Mi-Hee Kim; Bora Kwon; Kwang-Sang Kim; Min-Sook Kim; Min-Ji Kim; Hwa-Jin Kim; Da-In Choi; Miyeon Park; Moosung Kim; Min-Kyu Shin; Seung-Il Jeong; Kang-Yeol Yu; et al. (Natural Product Research, 2021)

Production of porphyra-334 in transgenic lines of Nannochloropsis salina by the expression of mycosporine-like amino acid biosynthetic genes of P. yezoensis - Jae-Sun In; Jong-Min Lim; Sokyong Jung; Dong-Woog Choi; Sung-Ran Min; Won-Joong Jeong (Journal of Applied Phycology, 2021)

Health risk assessment for multimedia exposure of formaldehyde emitted by chemical accident - Si-Hyun Park; Hui-Been Lim; Hyong-Jin Hong; Hee-Seok Kim; Dan-Ki Yoon; Hye-Won Lee; Hye-Kwan Kong; Jeong-In Jeon; Ji-Won Choi; Eun-Min Cho; Yong-Sung Cho; Cheol-Min Lee (Environmental Science and Pollution Research, 2021)

Cerebral glucose metabolism differs according to future weight change - Jeong Mi Kim; Minhee Jang; Eun Heui Kim; Mijin Kim; Su Jung Choi; Keunyoung Kim; Kyoungjune Pak; Yun Kyung Jeon; Sang Soo Kim; Bo Hyun Kim; Seong-Jang Kim; In Joo Kim (Brain Imaging and Behavior, 2020)

Targeting X chromosome-linked inhibitor of apoptosis protein in mucoepidermoid carcinoma of the head and neck: A novel therapeutic strategy using nitidine chloride - Hye-Jeong Kwon; Kyungsil Yoon; Ji-Youn Jung; Mi Heon Ryu; Sung-Hyun Kim; Eun-Seon Yoo; So-Young Choi; In-Hyoung Yang; Seong Doo Hong; Ji-Ae Shin; Sung-Dae Cho (Journal of Molecular Medicine, 2020)

Metformin ameliorates animal models of dermatitis - Soo Young Choi; Chanmi Lee; Min-Jeong Heo; Yeong Min Choi; In-sook An; Seunghee Bae; Sungkwan An; Jin Hyuk Jung (Inflammopharmacology, 2020)

High-density linkage map reveals QTL for Type-I seed coat cracking in RIL population of soybean [Glycine max (L.) Merr.] - Beom Kyu Kang; Jeong Hyun Seo; Hyun Jo; Krishnanand P. Kulkarni; Man Soo Choi; Hyun Tae Kim; Jeong Dong Lee; Sanjeev K. Dhungana; Hong Sik Kim; Jae Hyeon Oh; Ji Hee Park; Sang Ouk Shin; et al. (Euphytica, 2020)
Seed coat cracking (SCC), particularly the Type-I irregular cracking, is critical in determining the quality of appearance and commercial value of soybean seeds. The objective of this study was to identify the quantitative trait loci (QTLs) for SCC with high-density genetic map. One hundred sixty-seven recombinant inbred lines (RILs) developed from a cross between Uram (SCC-resistant) and Chamol (SCC-susceptible) were evaluated for SCC over 2 years (2016–2017). The QTL analysis identified 12 QTLs located on chromosomes 2 (D1b), 6 (C2), 8 (A2), 9 (K), 10 (O), 12 (H), 19 (L), and 20 (I). Out of the 12 QTLs, qSC2-1 , qSC9, SC10-1 , qSC10-2 , and qSC12 were novel QTLs and the other seven QTLs ( qSC2-2 , qSC2-3 , qSC6 , qSC8 , qSC19-1 , qSC19-2 , and qSC20 ) were found to co-localize with the previously identified QTLs. The mean SCC of the RILs of early maturity group was significantly higher than that of the late maturity group, suggesting an association between SCC and maturity loci. In addition, although 10 QTLs were distantly located from the maturity loci ( E1 , E3 , E4 , E7 , and E10 ), qSC10-1 and qSC10-2 co-localized with the maturity loci E2 . The results obtained in this study provide useful genetic information on SCC which could be used in the SCC breeding programs.

QTL mapping for pre-harvest sprouting resistance in japonica rice varieties utilizing genome re-sequencing - Kyeong-Seong Cheon; Yong Jae Won; Young-Min Jeong; Youn-Young Lee; Do-Yu Kang; Jun Oh; Hyoja Oh; Song Lim Kim; Nyunhee Kim; Eungyeong Lee; In Sun Yoon; Inchan Choi; et al. (Molecular Genetics and Genomics, 2020)
Pre-harvest sprouting (PHS) leads to serious economic losses because of reductions in yield and quality. To analyze the quantitative trait loci (QTLs) for PHS resistance in japonica rice, PHS rates on panicles were measured in 160 recombinant inbred lines (RILs) derived from a cross between the temperate japonica varieties Odae (PHS resistant) and Unbong40 (PHS susceptible) under two different environmental conditions—field (summer) and greenhouse (winter) environments. Genome re-sequencing of the parental varieties detected 266,773 DNA polymorphisms including 248,255 single nucleotide polymorphisms and 18,518 insertions/deletions. We constructed a genetic map comprising 239 kompetitive allele-specific PCR and 49 cleaved amplified polymorphic sequence markers. In the field environment, two major QTLs, qPHS-3 FD and qPHS-11 FD , were identified on chromosomes 3 and 11, respectively, whereas three major QTLs, qPHS-3 GH , qPHS-4 GH , and qPHS-11 GH , were identified on chromosomes 3, 4, and 11, respectively, in the greenhouse environment. qPHS-11 GH and qPHS-11 FD had similar locations on chromosome 11, suggesting the existence of a gene conferring stable PHS resistance effects under different environmental conditions. The QTLs identified in this study can be used to improve the PHS resistance of japonica varieties, and they may improve our understanding of the genetic basis of PHS resistance.

Waterlogging tolerance in apple trees grafted on rootstocks from G, CG, and M series - Byeong-Ho Choi; Narayan Bhusal; Woo-Tae Jeong; In-Hee Park; Su-Gon Han; Tae-Myung Yoon (Horticulture, Environment, and Biotechnology, 2020)

Hepatocyte CREBH deficiency aggravates inflammatory liver injury following chemokine-dependent neutrophil infiltration through upregulation of NF-κB p65 in mice - Jung-Ran Noh; Jae-Hoon Kim; Soon-Young Na; In Bok Lee; Yun Jeong Seo; Jung Hyeon Choi; Youngwon Seo; Tae Geol Lee; Hueng-Sik Choi; Yong-Hoon Kim; Chul-Ho Lee (Archives of Toxicology, 2020)

The medicinal mushroom Auricularia auricula - judae (Bull.) extract has antioxidant activity and promotes procollagen biosynthesis in HaCaT cells - Young-Ji Choi; In-Sun Park; Mi-Hee Kim; Bora Kwon; Young-Moo Choo; Seung-Il Jeong; Kang-Yeol Yu; Chung Hyeon Choe; Jiyoung Kim (Natural Product Research, 2019)

Combined Treatment with Low-Level Laser and rhBMP-2 Promotes Differentiation and Mineralization of Osteoblastic Cells under Hypoxic Stress - Jin-Ho Heo; Jeong-Hun Choi; In-Ryoung Kim; Bong-Soo Park; Yong-Deok Kim (Tissue Engineering and Regenerative Medicine, 2018)

Effects of CYP2C19 and CYP3A5 genetic polymorphisms on the pharmacokinetics of cilostazol and its active metabolites - Hye-In Lee; Ji-Young Byeon; Young-Hoon Kim; Choong-Min Lee; Chang-Ik Choi; Choon-Gon Jang; Jung-Woo Bae; Yun Jeong Lee; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2018)

Inverse agonist of ERRγ reduces cannabinoid receptor type 1-mediated induction of fibrinogen synthesis in mice with a high-fat diet-intoxicated liver - Yaochen Zhang; Don-Kyu Kim; Yoon Seok Jung; Yong-Hoon Kim; Yong Soo Lee; Jina Kim; Won-IL Jeong; In-Kyu Lee; Sung Jin Cho; Steven Dooley; Chul-Ho Lee; Hueng-Sik Choi (Archives of Toxicology, 2018)

Evidence of hepatitis E virus infection in specific pathogen-free rabbits in Korea - Sang-Hoon Han; Byung-Joo Park; Hee-Seop Ahn; Yong-Hyun Kim; Hyeon-Jeong Go; Dong-Hwi Kim; Joong-Bok Lee; Seung-Yong Park; Chang-Seon Song; Sang-Won Lee; In-Soo Choi (Virus Genes, 2018)

Neuronal loss and gliosis in the rat striatum subjected to 15 and 30 minutes of middle cerebral artery occlusion - Joon Ha Park; Jeong Hwi Cho; Ji Hyeon Ahn; Soo Young Choi; Tae-Kyeong Lee; Jae-Chul Lee; Bich Na Shin; Seongkweon Hong; Yong Hwan Jeon; Young-Myeong Kim; In Koo Hwang; Young Joo Lee; et al. (Metabolic Brain Disease, 2018)

Genetic variability comparison of cultured Israeli carp (Cyprinus carpio) from Korea using microsatellites - Jung Eun Kim; In Bon Goo; Ju-ae Hwang; Hyeong Su Kim; Hye-Sung Choi; Jeong-Ho Lee (Genes & Genomics, 2018)

Potential silver nanoparticles migration from commercially available polymeric baby products into food simulants - Jeong In Choi; Song Ji Chae; Jung Min Kim; Jae Chun Choi; Se Jong Park; Hee Ju Choi; Hojae Bae; Hyun Jin Park (Food Additives & Contaminants: Part A, 2018)

Resistance exercise improves cardiac function and mitochondrial efficiency in diabetic rat hearts - Tae Hee Ko; Jubert C. Marquez; Hyoung Kyu Kim; Seung Hun Jeong; SungRyul Lee; Jae Boum Youm; In Sung Song; Dae Yun Seo; Hye Jin Kim; Du Nam Won; Kyoung Im Cho; Mun Gi Choi; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Whole-genome sequence analysis of Zika virus, amplified from urine of traveler from the Philippines - Se Hun Gu; Dong Hyun Song; Daesang Lee; Jeyoun Jang; Min Young Kim; Jaehun Jung; Koung In Woo; Mirang Kim; Woong Seog; Hong Sang Oh; Byung Seop Choi; Jong-Seong Ahn; et al. (Virus Genes, 2017)

Roles of HIF-1α, VEGF, and NF-κB in Ischemic Preconditioning-Mediated Neuroprotection of Hippocampal CA1 Pyramidal Neurons Against a Subsequent Transient Cerebral Ischemia - Jae-Chul Lee; Hyun-Jin Tae; In Hye Kim; Jeong Hwi Cho; Tae-Kyeong Lee; Joon Ha Park; Ji Hyeon Ahn; Soo Young Choi; Hui Chen Bai; Bich-Na Shin; Geum-Sil Cho; Dae Won Kim; et al. (Molecular Neurobiology, 2017)

Overexpression of the OsbZIP66 transcription factor enhances drought tolerance of rice plants - Suin Yoon; Dong-Keun Lee; In Jeong Yu; Youn Shic Kim; Yang Do Choi; Ju-Kon Kim (Plant Biotechnology Reports, 2017)

Clozapine Improves Memory Impairment and Reduces Aβ Level in the Tg-APPswe/PS1dE9 Mouse Model of Alzheimer’s Disease - Yura Choi; Ha Jin Jeong; Quan Feng Liu; Seung Tack Oh; Byung-Soo Koo; Yeni Kim; In-Won Chung; Yong Sik Kim; Songhee Jeon (Molecular Neurobiology, 2017)

2-(4-{2-[(phenylthio)acetyl]carbonohydrazonoyl}phenoxy)acetamide as a new lead compound for management of allergic rhinitis - Hee-Yun Kim; Sun-Young Nam; Jae-Bum Jang; Youngjin Choi; In-Cheol Kang; Hyung-Min Kim; Hyun-Ja Jeong (Inflammation Research, 2016)

Genetic analysis of COL11A2 in Korean patients with autosomal dominant non-syndromic hearing loss - Sang-Joo Kim; Hong-Joon Park; Borum Sagong; Seung-Hyun Bae; Se-Kyung Oh; Jeong-In Baek; Jae Young Choi; Kyu-Yup Lee; Un-Kyung Kim (Genes & Genomics, 2016)

Effects of Chronic Scopolamine Treatment on Cognitive Impairments and Myelin Basic Protein Expression in the Mouse Hippocampus - Joon Ha Park; Hyun Young Choi; Jeong-Hwi Cho; In Hye Kim; Tae-Kyeong Lee; Jae-Chul Lee; Moo-Ho Won; Bai Hui Chen; Bich-Na Shin; Ji Hyeon Ahn; Hyun-Jin Tae; Jung Hoon Choi; et al. (Journal of Molecular Neuroscience, 2016)

Mesenchymal signaling in dorsoventral differentiation of palatal epithelium - Wern-Joo Sohn; Gi-Jeong Gwon; Hyeng-Soo Kim; Sanjiv Neupane; Sung-Jin Cho; Jae-Hyung Lee; Hitoshi Yamamoto; Je-Yong Choi; Chang-Hyeon An; Youngkyun Lee; Hong-In Shin; Sanggyu Lee; et al. (Cell and Tissue Research, 2015)

Serological surveillance studies confirm the Rift Valley fever virus free status in South Korea - Hyun Joo Kim; Jee-Yong Park; Hye-Young Jeoung; Jung-Yong Yeh; Yun-Sang Cho; Jeong-Soo Choi; Ji-Youn Lee; In-Soo Cho; Han-Sang Yoo (Tropical Animal Health and Production, 2015)

Erratum to: Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Coix seed extract attenuates the high-fat induced mouse obesity via PPARγ and C/EBPα a downregulation - Eun-Kyeong Choi; Yu Jeong Cho; Hea Jung Yang; Ki-Suk Kim; In-Seung Lee; Jong-Chan Jang; Kang-Hoon Kim; Ji Hyun Bang; Yumi Kim; Se Hoon Kim; Young-Hwan Cho; Na Young Yoon; et al. (Molecular & Cellular Toxicology, 2015)

Changes in weather and climate extremes over Korea and possible causes: A review - Seung-Ki Min; Seok-Woo Son; Kyong-Hwan Seo; Jong-Seong Kug; Soon-Il An; Yong-Sang Choi; Jee-Hoon Jeong; Baek-Min Kim; Ji-Won Kim; Yeon-Hee Kim; June-Yi Lee; Myong-In Lee (Asia-Pacific Journal of Atmospheric Sciences, 2015)

Changes of volatile compounds in vitis labrusca ‘Doonuri’ grapes during stages of fruit development and in wine - Eun-Ha Chang; Sung-Min Jeong; Youn-Young Hur; Sang-Wook Koh; In-Myung Choi (Horticulture, Environment, and Biotechnology, 2015)

Analysis of an ECG Record Database Reveals QT Interval Prolongation Potential of Famotidine in a Large Korean Population - Jaesuk Yun; Eun Hwangbo; Jongpill Lee; Chong-Run Chon; Peol A. Kim; In-Hye Jeong; Manyoung Park; Raewoong Park; Shin-Jung Kang; Donwoong Choi (Cardiovascular Toxicology, 2015)

Manufacture of duck-beak bone particles with gamma-ray irradiation for bone graft - Se Eun Kim; Kyung Mi Shim; Seok Hwa Choi; Sung In Jeong; Jun Sik Son; Youn-Mook Lim; Seong Soo Kang (Tissue Engineering and Regenerative Medicine, 2014)

감마선 조사에 의한 조직공학용 알긴산 나노섬유의 분해 영향 - Sung In Jeong; Jong-Bae Choi; Young Min Shin; Jong-Seok Park; Hui-Jeong Gwon; Young-Chang Nho; Seong Soo Kang; Youn-Mook Lim (Tissue Engineering and Regenerative Medicine, 2014)

감마선 조사에 의한 헤파린이 도입된 박테리아 셀룰로오스의 골조 직공학용 지지체로서의 개발 및 특성분석 - Sung In Jeong; Jin-Oh Jeong; Jong-Bae Choi; Young Min Shin; Jong-Seok Park; Hui-Jeong Gwon; Young-Chang Nho; Sung-Jun An; Man-Young Park; Youn-Mook Lim (Tissue Engineering and Regenerative Medicine, 2014)

Biocompatible Glycol Chitosan-Coated Gold Nanoparticles for Tumor-Targeting CT Imaging - In-Cheol Sun; Jin Hee Na; Seo Young Jeong; Dong-Eog Kim; Ick Chan Kwon; Kuiwon Choi; Cheol-Hee Ahn; Kwangmeyung Kim (Pharmaceutical Research, 2014)

Characterization of SMV resistance of soybean produced by genetic transformation of SMV-CP gene in RNAi - Hye Jeong Kim; Mi-Jin Kim; Jung Hun Pak; Ho Won Jung; Hong Kyu Choi; Yeong-Hoon Lee; In-Youl Baek; Jong-Min Ko; Soon-Chun Jeong; In Sook Pack; Ki Hyun Ryu; Young-Soo Chung (Plant Biotechnology Reports, 2013)

The prevalence of BRCA mutations among familial breast cancer patients in Korea: results of the Korean Hereditary Breast Cancer study - Sang-Ah Han; Sung-Won Kim; Eunyoung Kang; Sue K. Park; Sei-Hyun Ahn; Min Hyuk Lee; Seok-Jin Nam; Wonshik Han; Young Tae Bae; Hyun-Ah Kim; Young Up Cho; Myung Chul Chang; et al. (Familial Cancer, 2013)

A novel gibberellin 2-oxidase gene CaGA2ox1 in pepper is specifically induced by incompatible plant pathogens - Yeon Lee; Young-Cheol Kim; Soo Yong Kim; In-Jung Lee; Doil Choi; Kyung-Hee Paek; Hye Sun Cho; Suk Yoon Kweon; Jeong Mee Park (Plant Biotechnology Reports, 2012)

An efficient selection and regeneration protocol for Agrobacterium-mediated transformation of oriental melon (Cucumis melo L. var. makuwa) - Jun Young Choi; Jeong Sheop Shin; Young Soo Chung; Nam-In Hyung (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

CYP2C9*3 and *13 alleles significantly affect the pharmacokinetics of irbesartan in healthy Korean subjects - Chang-Ik Choi; Mi-Jeong Kim; Eun-Kyung Chung; Hye-In Lee; Choon-Gon Jang; Jung-Woo Bae; Seok-Yong Lee (European Journal of Clinical Pharmacology, 2012)

Comparative analysis of expressed sequence tags (ESTs) between normal group and softness syndrome group in Halocynthia roretzi - Ji Eun Jeong; Se Won Kang; Yun Kyung Shin; Je Cheon Jun; Young-Ok Kim; Young Baek Hur; Jae-Hyung Kim; Sung-Hwa Chae; Jun-Sang Lee; In ho Choi; Yeon Soo Han; Dae-Hyun Seog; et al. (Molecular & Cellular Toxicology, 2011)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Polymorph Transformation in Paracetamol Monitored by In-line NIR Spectroscopy During a Cooling Crystallization Process - In-Chun Wang; Min-Jeong Lee; Da-Young Seo; Hea-Eun Lee; Yongsun Choi; Woo-Sik Kim; Chang-Sam Kim; Myung-Yung Jeong; Guang Jin Choi (AAPS PharmSciTech, 2011)

Anti-angiogenic effects of the water extract of HangAmDan (WEHAD), a Korean traditional medicine - Ji-Young Bang; Kyung-Soon Kim; Eung-Yoon Kim; Hwa-Seung Yoo; Yeon-Weol Lee; Chong-Kwan Cho; YoungJin Choi; Hyun-Ja Jeong; In-Cheol Kang (Science China Life Sciences, 2011)

A possible association of EMID2 polymorphisms with aspirin hypersensitivity in asthma - Charisse Flerida A. Pasaje; Jeong-Hyun Kim; Byung-Lae Park; Hyun Sub Cheong; Mi-Kyeong Kim; Inseon S. Choi; Sang Heon Cho; Chein-Soo Hong; Yong Won Lee; Jae-Young Lee; In Song Koh; Tae-Joon Park; et al. (Immunogenetics, 2011)

Ailanthus altissima swingle has anti-anaphylactic effect and inhibits inflammatory cytokine expression via suppression of nuclear factor-kappaB activation - Tae-Hee Kang; In-Young Choi; Su-Jin Kim; Phil-Dong Moon; Jae-Uk Seo; Jae-Joong Kim; Nyeon-Hyung An; Sung-Hoon Kim; Min-Ho Kim; Jae-Young Um; Seung-Heon Hong; Hyung-Min Kim; et al. (In Vitro Cellular & Developmental Biology - Animal, 2010)

Assessment of Gene Flow from Genetically Modified Anthracnose-Resistant Chili Pepper (Capsicum annuum L.) to a Conventional Crop - Chang-Gi Kim; Dae In Kim; Hyo-Jeong Kim; Ji Eun Park; Bumkyu Lee; Kee Woong Park; Soon-Chun Jeong; Kyung Hwa Choi; Joo Hee An; Kang-Hyun Cho; Young Soon Kim; Hwan Mook Kim (Journal of Plant Biology, 2009)

Green tea seed oil reduces weight gain in C57BL/6J mice and influences adipocyte differentiation by suppressing peroxisome proliferator-activated receptor-γ - Na-Hyung Kim; Sun-Kyung Choi; Su-Jin Kim; Phil-Dong Moon; Hun-Sun Lim; In-Young Choi; Ho-Jeong Na; Hyo-Jin An; Noh-Yil Myung; Hyun-Ja Jeong; Jae-Young Um; Seung-Heon Hong; et al. (Pflügers Archiv - European Journal of Physiology, 2008)

Involvement of p38 MAPK-mediated signaling in the calpeptin-mediated suppression of myogenic differentiation and fusion in C2C12 cells - Sung-Ho Kook; Ki-Choon Choi; Young-Ok Son; Kyung-Yeol Lee; In-Ho Hwang; Hyun-Jeong Lee; Wan-Tae Chung; Choon-Bong Lee; Jong-Sun Park; Jeong-Chae Lee (Molecular and Cellular Biochemistry, 2008)

Cyclic mechanical stress suppresses myogenic differentiation of adult bovine satellite cells through activation of extracellular signal-regulated kinase - Sung-Ho Kook; Young-Ok Son; Ki-Choon Choi; Hyun-Jeong Lee; Wan-Tae Chung; In-Ho Hwang; Jeong-Chae Lee (Molecular and Cellular Biochemistry, 2008)

Hesperidin inhibits expression of hypoxia inducible factor-1 alpha and inflammatory cytokine production from mast cells - In-Young Choi; Su-Jin Kim; Hyun-Ja Jeong; Seong-Heak Park; Yong-Sun Song; Ji-Hyun Lee; Tae-Hee Kang; Jin-Han Park; Gab-Soo Hwang; Eon-Jeong Lee; Seung-Heon Hong; Hyung-Min Kim; et al. (Molecular and Cellular Biochemistry, 2007)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Constitutive expression of two pathogenesis-related genes in tomato plants enhanced resistance to oomycete pathogen Phytophthora capsici - Sujon Sarowar; Young Jin Kim; Eui Nam Kim; Ki Deok Kim; Jun Young Choi; Nam In Hyung; Jeong Sheop Shin (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

Biflavonoids inhibited phosphatase of regenerating liver-3 (PRL-3) - Sung-Kyu Choi; Hyun-Mi Oh; Su-Kyung Lee; Dae Gwin Jeong; Seong Eon Ryu; Kwang-Hee Son; Dong Cho Han; Nack-Do Sung; Nam-In Baek; Byoung-Mog Kwon (Natural Product Research, 2006)

Cyclic diarylheptanoids inhibit cell-mediated low-density lipoprotein oxidation - Hyun-Mi Kang; Ju Ryong Kim; Tae-Sook Jeong; Sung-Gyu Choi; Young-Han Ryu; Goo Taeg Oh; Nam-In Baek; Byoung-Mog Kwon (Natural Product Research, 2006)

Subcellular accumulation of Cu in the Antarctic bivalve Laternula elliptica from a naturally Cu-elevated bay of King George Island - Heeseon J. Choi; In-Young Ahn; Ko-Woon Kim; Yong-Suk Lee; In-Sook Lee; Kye-Heon Jeong (Polar Biology, 2003)

Production of herbicide-resistant transgenic Panax ginseng through the introduction of the phosphinothricin acetyl transferase gene and successful soil transfer - Y. Choi; J. Jeong; J. In; D. Yang (Plant Cell Reports, 2003)

A new class II rice chitinase, Rcht2, whose induction by fungal elicitor is abolished by protein phosphatase 1 and 2A inhibitor - Cha Young Kim; Sang Wan Gal; Mi Sook Choe; Sun Yong Jeong; Soo In Lee; Yong Hwa Cheong; Sang Hyoung Lee; Young Ju Choi; Chang-deok Han; Kyu Young Kang; Moo Je Cho (Plant Molecular Biology, 1998)